2017
DOI: 10.1371/journal.pone.0172718
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sevuparin on rosette formation and cytoadherence of Plasmodium falciparum infected erythrocytes

Abstract: In severe falciparum malaria cytoadherence of parasitised red blood cells (PRBCs) to vascular endothelium (causing sequestration) and to uninfected red cells (causing rosette formation) contribute to microcirculatory flow obstruction in vital organs. Heparin can reverse the underlying ligand-receptor interactions, but may increase the bleeding risks. As a heparin-derived polysaccharide, sevuparin has been designed to retain anti-adhesive properties, while the antithrombin-binding domains have been eliminated, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 60 publications
0
25
1
Order By: Relevance
“…Non-anticoagulant heparins prevent histone-induced lethality in bacterial sepsis models in vivo ( Wildhagen et al , 2014 ) and block the toxic effects of plasmodial histones in vitro . A non-anticoagulant heparin, Sevuparin, is being used in phase II trials for malaria for its potential to block parasite binding ( Leitgeb et al , 2017 ; Saiwaew et al , 2017 ). Based on the work in this paper, an option would be to consider a combination therapy, based on stopping the thrombin-mediated effect using a PAR1 inhibitor combined with a non-anti-coagulant heparin to mitigate the histone effect.…”
Section: Discussionmentioning
confidence: 99%
“…Non-anticoagulant heparins prevent histone-induced lethality in bacterial sepsis models in vivo ( Wildhagen et al , 2014 ) and block the toxic effects of plasmodial histones in vitro . A non-anticoagulant heparin, Sevuparin, is being used in phase II trials for malaria for its potential to block parasite binding ( Leitgeb et al , 2017 ; Saiwaew et al , 2017 ). Based on the work in this paper, an option would be to consider a combination therapy, based on stopping the thrombin-mediated effect using a PAR1 inhibitor combined with a non-anti-coagulant heparin to mitigate the histone effect.…”
Section: Discussionmentioning
confidence: 99%
“…headache [ 66 ] Prevention (travellers’ market) and partner drug in combination therapy AQ-13 Immtech and Tulane University Modified 4-aminoquinoline Blood schizonticide for falciparum and vivax HAV study published in 2007 showed a similar tolerability and PK profile to chloroquine [ 70 ] Mean PCT 47.3 h (43.5–51.1) vs 32.5 (28.0–37.0) for artemether–lumefantrine (AL): by day 42, 0/28 vs 2/33 recrudescences in AL arm [ 69 ] No grade 2–4 adverse events [ 69 ] Partner drug in combination therapy Methylene Blue University of Heidelberg Phenothiazine derivative. Prevents haem polymerisation by inhibiting P. falciparum glutathione reductase PF schizonticide and potent gametocytocidal agent (male and female Stage V gametocytes) First description of methylene blue to treat malaria was in 1891 [ 131 ] D28 ACPR 72–84% in semi-immune adults [ 132 ]; 95% in combination with amodiaquine [ 133 ] Increased vomiting when combined with artesunate–amodiaquine [ 82 ] Part of a triple combination with ACTs + transmission blocking Sevuparin (DF02) Dilaforette-Karolinska Institute Anti-adhesive polysaccharide derived from heparin with eliminated antithrombin binding site [ 87 ] Blocks merozoite invasion and sequestration [ 87 ] Well tolerated in HAVs [ 87 ] ≥ 100 μg/mL inhibits cytoadherence [ 86 ]. No significant difference in parasite clearance between sevuparin-atovaquone–proguanil (AP) vs AP alone [ 87 ] No adverse event leading to study withdrawal.…”
Section: Drugs In Clinical Developmentmentioning
confidence: 99%
“…The search for adjunctive therapies capable of improving the outcome from severe malaria continues after serial alternatives have failed to show any benefit, or in some cases, caused harm [ 16 ]. Sevuparin is a polysaccharide heparin analogue, which retains the anti-adhesive effects of heparin without the antithrombin properties and has been shown to block merozoite invasion, cytoadherence and rosetting [ 86 , 87 ]. Studies in patients with severe malaria are planned.…”
Section: Drugs In Clinical Developmentmentioning
confidence: 99%
“…Neither of these treatments showed beneficial effect on clinical, haemostatic or parasitic parameters. Sulfated glycosaminoglycans (GAG), including heparin and sevuparin, can disrupt rosette formation and inhibit cytoadherence to endothelial cells, and have been proposed as potential adjunctive therapy [ 54 , 55 ]. However, only one study examined their effects in a RCT.…”
Section: Introductionmentioning
confidence: 99%